The E-Book of Modern Standard Arabic for Arabic Teaching Based on Rushdi Ahmed Tuaima's Theory - Ahmad Nuruddin Thaifur; Ahmad Nur (State Islamic University (UIN) of Sunan Ampel Surabaya, Indonesia, 2022)
This study aims to determine the value of modern standard Arabic (MSA); an electronic book was written by Eckehard Schulz, as evidenced by Rusydi’s work in preparing educational materials for Arabic language education programs. Among the book's values ​​are excellent books based on the composition of the material, following the evidence of Rushdi's work in preparing educational materials for Arabic language education programs. This value consists of general data, outputs, basics of book preparation, book language, language skills, cultural teaching, and exercises. The researcher conducted a descriptive literature study, and the results of this study were to find out the advantages provided by the MSA. The problems discussed in this study are: How to analyze and evaluate the electronic book MSA. What is the value of the e-book MSA as evidenced by Tuaima's work in preparing educational materials for Arabic language education programs? To answer these problems, researchers used research tools: observation and interviews. تهدف هذه الدراسة إلى معرفة قيمة الكتاب الإلكتروني